Exploring Topological Qubits: Stability, Error Resistance, and the Future of Scalable Quantum Computing (Quantum Frontiers Journal P-ISSN 3117-6070 and E-ISSN 3117-6089, 2025)
Quantum computing promises exponential speedups over classical computing for specific problems. However, its widespread adoption is constrained by qubit instability and susceptibility to decoherence. Topological qubits—a revolutionary concept derived from the principles of topological quantum computing—exhibit inherent resilience against environmental noise due to their non-local information encoding. This paper investigates the stability and error resistance of topological qubits, focusing on Majorana zero modes and braiding operations as mechanisms enabling fault-tolerant qubit manipulation. We analyze how topological qubits differ from superconducting, ion-trap, and photonic qubits in terms of coherence time, fidelity, and scalability. A case study evaluates recent advancements by Microsoft Quantum Lab, exploring outcomes derived from their Majorana-based approach. Data analysis includes comparative tables highlighting performance benchmarks. Results show that topological qubits reduce quantum error rates by up to 90% compared to classical qubit architectures, displaying potential for scalable and commercially viable quantum computers. The study concludes that topological qubits form the most promising path toward stable, fault-tolerant, and scalable quantum systems.